Artificial placenta support of extremely preterm ovine fetuses at the border of viability for up to 336 hours with maintenance of systemic circulation but reduced somatic and organ growth - Usuda, Haruo; Ikeda, Hideyuki; Watanabe, Shimpei; Sato, Shinichi; Fee, Erin L.; Carter, Sean W. D.; Kumagai, Yusaku; Saito, Yuya; Takahashi, Tsukasa; Takahashi, Yuki; Kawamura, Shinichi; Hanita, Takushi; et al. (Frontiers in Physiology, 2023)
Introduction: Artificial placenta therapy (APT) is an experimental life support system to improve outcomes for extremely preterm infants (EPI) less than 1000 g by obviating the need for pulmonary gas exchange. There are presently no long-term survival data for EPI supported with APT. To address this, we aimed to maintain 95d-GA (GA; term-150d) sheep fetuses for up to two weeks using our APT system. Methods: Pregnant ewes (n=6) carrying singleton fetuses underwent surgical delivery at 95d GA. Fetuses were adapted to APT and maintained for up to two weeks with constant monitoring of key physiological parameters and extensive time-course blood and urine sampling, and ultrasound assessments. Six age-matched in-utero fetuses served as controls. Data were tested for group differences with ANOVA. Results: Six APT Group fetuses (100%) were adapted to APT successfully. Mean BW at the initiation of APT was 656 ± 42 g. Mean survival was 250 ± 72 h (Max 336 h) with systemic circulation and key physiological parameters maintained mostly within normal ranges. APT fetuses had active movements and urine output constantly exceeded infusion volume over the experiment. At delivery, there were no differences in BW (with edema in three APT group animals), brain weight or femur length between APT and in-utero Control animals. Organ weights and humerus lengths were significantly reduced in APT group (p<0.05). Albumin, IGF-1 and phosphorus were significantly decreased in APT group (p<0.05). No cases of positive blood culture were detected. Conclusions: We report the longest use of APT to maintain extremely preterm fetuses to date. Fetal systemic circulation was maintained without infection, but growth was abnormal. This achievement suggests a need to focus not only on cardiovascular stability and health but also on the optimization of fetal growth and organ development. This new challenge will need to be overcome prior to the clinical translation of this technology.